Presencia de Lomentaria hakodatensis Yendo 1920 (Lomentariaceae, Rhodophyta) en la costa de Asturias (Norte de España). First report of Lomentaria hakodatensis Yendo 1920 from the Asturian coast (North of Spain) - Lamela, Cristina; Fernández, Consolación; Rico, José Manuel (Acta Botanica Malacitana, 2012)
First report of Lomentaria hakodatensis Yendo 1920 from the Asturian coast (North of Spain) Palabras clave. Lomentaria hakodatensis, Lomentariaceae, Rhodophyta, especies introducidas, Asturias, Norte de España Key words. Lomentaria hakodatensis , Lomentariaceae, Rhodophyta, alien species, Asturias, N. Spain